Synthesis and characterization of bismuth tantalate binary materials for potential application in multilayer ceramic capacitors (MLCC) - Tan, Kar Ban; F. G., Anna; Zainal, Zulkarnain (Penerbit Universiti Sains Malaysia, 2008)
The single phase bismuth tantalate (BiTaO4) was successfully synthesized by conventional solid-state method at sintering temperature 1100oC. This material crystallized in a triclinic system, space group Pī with a = 7.6585 Ǻ, b = 5.5825 Ǻ, c = 7.7795 Ǻ, α = 90.03o, β = 77.04o and γ = 86.48o, respectively. The electrical properties of BiTaO4 were characterized by AC impedance analyzer, HP4192 at temperature ranging from 25oC–850oC over frequency range of 5–13 MHz. The sample was highly resistive as the conductivities were unlikely to be determined below 550oC. On the other hand, BiTaO4 exhibited moderate dielectric constant, εr = 47 at ambient temperature in the frequency region of 1 MHz and near zero temperature coefficient of capacitance (TCC), 0.00022, making it a potential candidate for multilayer ceramic capacitors (MLCC).